A Green Light Sensitive Au/PBTTT-C14/OTS/SiO2/Si/Ag MOS Capacitor - Singh A.K.; Pandey A.; Chakrabarti P. (My University, 2025)
The present article demonstrates a simple method to fabricate Au/PBTTT-C14/OTS/SiO2/Si/Ag-based MOS capacitor using the floating transfer method (FTM) for deposition of PBTTT-C14 and investigates the mechanism of high-frequency operation at quasi-static state at room temperature (25°C). The good quality and homogeneous nature of FTM grown film enhance the interface quality of the device. The surface morphology and absorption properties of the fabricated device were characterized by AFM and UV-Visible absorption. The electrical characterization of the MOS device was done by using Au and Ag electrodes. The charge concentration in polymer and interface property of Organic polymer/octadecyl trichlorosilane treated SiO2 have been investigated systematically. The MOS device has been examined under dark and green light (550 nm) illumination. The device exhibits strong responsivity and photosensitivity to green light. © 1989-2012 IEEE.